Managing Amphibian Disease with Skin Microbiota. Issue 3 (March 2016) - Woodhams, Douglas C.; Bletz, Molly; Kueneman, Jordan; McKenzie, Valerie
Abstract : The contribution of emerging amphibian diseases to the sixth mass extinction is driving innovative wildlife management strategies, including the use of probiotics. Bioaugmentation of the skin mucosome, a dynamic environment including host and microbial components, may not provide a generalized solution. Multi-omics technologies and ecological context underlie effective implementation.